Self-coping mechanism as a mediator between financial strains and financial security of single mothers in Malaysia - Ahmad, Siti Yuliandi; Sabri, Mohamad Fazli; Abdul Rahim @ Abdul Wahab, Husniyah; Osman, Syuhaily (Malaysian Consumer and Family Economics Association, 2018)
The main objective of this study was to examine the psychological aspect of self-coping mechanisms in influencing the relationship between financial strains and financial security of single mothers. A multistage random sampling was used to gather the data of 600 single mothers from six single mother associations registered under the Ministry of Women, Family and Community Development in Malaysia. The data were statistically analysed using descriptive analysis of Pearson Product Moment Correlation and Structural Equation Modelling. There were positive significant relationships found between self-coping mechanisms, financial strains, and financial security. The structural equation of financial security model showed a relatively good fit to the data obtained in the study. The self-coping mechanisms were distinguished as a mediator in the relationships between financial strains and financial security. The self-coping mechanisms illustrated a moderate relationship (r = 0.427) in the financial security model. In testing the mediation effect, the indirect mediation existed in the relationships between financial strains and financial security. The findings of this have implied that single mother required coping strategies such as social support program or financial education. This study seems to support the importance of behavioural finance in line with notable empirical findings and the theoretical reasoning in understanding financial security of single mothers. Thus, government and non-profit organisation play crucial role to provide social support programme and financial education programme for single mothers.